2012
DOI: 10.3390/su4071510
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Potential of Climate Change Mitigation Actions in Three Different City Types in Finland

Abstract: Abstract:As the effects of global warming have become more evident, ambitious short-term greenhouse gas emission reduction targets have been set in recent years. Many cities worldwide have adopted an active approach to climate change mitigation, but policy makers are not always knowledgeable of the true effects of their planned mitigation action. The purpose of this paper is to evaluate the effectiveness of different mitigation strategies in achieving low-carbon urban communities. The assessment is conducted v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 26 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…In addition to carbon pricing and urban planning, there are behavioral and technological policy suggestions for cities in the literature. In particular local renewable energy production is promoted (Kyrö et al 2012, Li et al 2015, Maraseni et al 2016a. Several authors highlight that cleaner energy production not only reduces the CBCF of the city residents, but that the benefits spread outside the city region as well when the goods and services produced within the city are consumed by the residents of other areas (Hu et al 2016, Laine et al 2017, Lin et al 2017.…”
Section: City Policiesmentioning
confidence: 99%
“…In addition to carbon pricing and urban planning, there are behavioral and technological policy suggestions for cities in the literature. In particular local renewable energy production is promoted (Kyrö et al 2012, Li et al 2015, Maraseni et al 2016a. Several authors highlight that cleaner energy production not only reduces the CBCF of the city residents, but that the benefits spread outside the city region as well when the goods and services produced within the city are consumed by the residents of other areas (Hu et al 2016, Laine et al 2017, Lin et al 2017.…”
Section: City Policiesmentioning
confidence: 99%
“…Some focused on reducing carbon emissions through technological measures and policies, including the development of new energy vehicles [14], improvement in energy efficiency [15], congestion charges [16,17], and the use of public transport [18]. Other studies have found that a dense urban structure can be an effective way to reduce carbon emissions [19][20][21][22]. However, the current level of understanding about the effect of urban form on carbon emissions should be strengthened, as others have found ambiguous relationships between land use and transport [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%